HUBUNGAN ANTARA DURASI PENGGUNAAN SMARTPHONE DENGAN KELUHAN NYERI LEHER PADA TIM E-SPORT MOBILE LEGENDS UPN VETERAN JAKARTA - Sheilla Maurie Arthamevia, (2022)
Background : Smartphones are a tangible manifestation of technological advances, devices that work very complex, internet access, social media, and game applications. E-sports or cybersports, virtual sports, and competitive games, which are video game competitions. E-sport is connected to the internet network. Musculoskeletal disorders related to the use of computers and smartphones cause neck muscle fatigue caused by poor posture and for a long time resulting in muscle tension. The duration of cell phone use is a big factor in determining neck pain. Objective : The purpose of this study was to determine the relationship between the duration of smartphone use and neck pain in the Mobile Legends E-sport Team UPN Veteran Jakarta. Methods : The design of this research is a cross-sectional study through a questionnaire. The parameters used to measure the duration of smartphone use are hours and pain using NRS (Numeric Rating Scale). Results : Based on the results of SPSS 25 data, the correlation coefficient of Pearson Correlation NRS is obtained with a value of p = 1 and the duration of smartphone use with a value of p = 0.341. Conclusion : The conclusion is that the duration of smartphone use with neck pain has a relationship with the level of a weak relationship.